Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/1471-0528.12455
|View full text |Cite
|
Sign up to set email alerts
|

The effect of method and gestational age at termination of pregnancy on future obstetric and perinatal outcomes: a register‐based cohort study in Aberdeen, Scotland

Abstract: Objective To determine whether termination of pregnancy (TOP), including the method used or gestational age at termination, affects future obstetric and perinatal outcomes.Design Register-based cohort.Setting Aberdeen Maternity Hospital, Scotland, UK.Population From the Aberdeen Maternity and Neonatal Databank (AMND) we identified 3186 women who had terminated their first pregnancy and then had a second pregnancy of beyond 24 weeks of gestation between 1986 and 2010. We identified 42 446 women who had their fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(86 reference statements)
2
10
0
Order By: Relevance
“…However, it has been reported that multiple surgical abortions may increase the chance of late miscarriage in any future pregnancy,3 although evidence is conflicting 4 5. It has also been reported to increase the risk of very preterm birth,6 although other studies7 8 contradict this. However, it is reasonable to assume that reducing the rates of women undergoing multiple surgical abortions would be of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that multiple surgical abortions may increase the chance of late miscarriage in any future pregnancy,3 although evidence is conflicting 4 5. It has also been reported to increase the risk of very preterm birth,6 although other studies7 8 contradict this. However, it is reasonable to assume that reducing the rates of women undergoing multiple surgical abortions would be of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies revealed that abortions have been associated with perinatal risk . However, very few studies explored the risk of second‐trimester abortion on subsequent birth . Of the few studies available, some were based on surgical abortion, and very few were based on medical abortion .…”
Section: Discussionmentioning
confidence: 99%
“…Of the few studies available, some were based on surgical abortion, and very few were based on medical abortion . Most of them were limited by small sample size or lack of a comparison group, and others lack the adjustments for potential confounders such as smoking, interval between pregnancies and methods of abortion . This study is the largest of its kind that could partly control for the potential confounders with more birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations